(untitled) (Bangladesh Medical Journal Khulna, 2020)
Background: Community acquired pneumonia (CAP) is a leading cause of morbidity and mortality in Bangladesh. There is difficulty in identification of the causative organism due to lack of facility of sputum culture and sensitivity test in many hospitals of Bangladesh. So targeted anti microbial therapy is not possible and empirical antibiotic prescription is done. The choice of empirical selection of antibiotic should be the best effective drug for the treatment of CAP. Objective: To assess the efficacy of selected empirical antibiotic selection for the treatment of CAP. Methods: This prospective observational study involves 82 patients with CAP admitted in medicine ward of Khulna medical college hospital, Khulna, Bangladesh. Patients were selected by inclusion and exclusion criteria. Diagnosis of CAP was confirmed by chest x-ray. Empirical selection of antibiotic was based on clinical experience. Most of the patients were treated with combined antibiotic except a few with monotherapy. Evaluation of the empirical choice of ant biotic was done by the outcome. Data of different parameter were recorded during study in preformed proforma. Statistical analysis was done by using SPSS. Result: Out of 82 patients 62 (76%) were male and 20 (24%) were female. Mean age was 54.4 (± 9.6) years. Duration of antibiotic treatment was 7 days. No drug related adverse effect was observed. One patient developed paraneumonic effusion and none of the patient developed lung parenchymal damage or lung abscess. All the patient recovered completely. Conclusion: CAP is treated in many hospitals of Bangladesh by selecting the antibiotic empirically. Improvement of hospital laboratories to perform sputum for culture and sensitivity test is necessary for selecting an effective anti biotic. Bang Med J (Khulna) 2019; 52 : 25-29